Metamorphosis of Healing: Medicine, Divine Healing and Divine Health, the Place of Faith and the Word among African Pentecostals and Charismatics - Ayivor, Samora Harry (Transformation, 2025)
Divine healing is the belief in receiving healing of an illness through God's supernatural power without biomedicines or herbs. However, the concept of health and healing has evolved over the years. Many Pentecostals and Charismatics now advocate for seeking God's ‘best’ and believe that divine healing is God's ‘good’ will for His children. However, divine health, a state of constant well-being without illness, is God's ‘perfect’ will for his children. Based on research conducted in Accra, Ghana, between May and June 2024, this study examines how Pentecostals have broadened the scope of healing. The findings demonstrate that while Pentecostals believe in divine healing, they aspire to achieve a higher state of well-being – divine health. The paper also reveals that Pentecostals rely on faith in the Word of God as the primary means to pursue divine health and incorporate practices such as prayer, meditation, “soaking” the Word, and positive confession.